Data base of Contextual interference in motor skills performance: a meta-analysis review - Jiménez Díaz, Judith (2020)
This study expands a meta-analysis research done recently examining the Contextual Interference (CI) Effect using a meta-analytic technique. After a literature review in eleven digital databases and references, 25 research accomplished with the established inclusion criteria for the intra-group analysis while 21 corresponded for the inter-groups. Based on random practice models (RP), it was found 150 individual Effect Size (ES) for the intra- group design. It was also found that the blocked practice (BP) improved its acquisition skills (ES= 0.69; n= 39; IC95%= 0.40 a 0.97) and decreased in retention (ES= 0.12; n= 37; IC95%= -0.12 a 0.38). For the inter-group design, we had a total of 68 individual ES finding that in acquisition the BP revealed a better performance than RP (ES = -0.15; n= 31; IC95%= -0.32 a -0.01) and in retention both groups had similar performance (ES = -0.02; n= 37; IC95%= -0.20 a 0.26). Results support (CI) effect in acquisition. The presence of moderate variables (participants ‘age, number of attempts, type of skill and research´s external validity) confirm that this effect can be generalized.